The Life and Lies of Paul Crouch : Communist, Opportunist, Cold War Snitch - Taylor, Gregory S. (Book collections on Project MUSE., 2014)
Taylor traces the life of Paul Crouch (1903-1955), an infamous paid informant for the federal government during the McCarthy era. Taylor not only highlights Crouch's unusual life, but also examines the dangers of ideologues.